2017
DOI: 10.3168/jds.2016-11886
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen utilization, preweaning nutrient digestibility, and growth effects of Holstein dairy calves fed 2 amounts of a moderately high protein or conventional milk replacer

Abstract: Studies have shown that calves fed milk replacers (MR) with crude protein (CP) concentrations greater than 20%, as typically found in conventional MR, have higher dry matter intakes (DMI) and greater average daily gains (ADG) but consume less starter, which can lead to stress during weaning and reduced rumen development. The greater amount of CP being fed to preweaned calves may alter their nitrogen (N) balance, and excess N may be excreted in the urine. The objective of this study was to determine N utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
11
17
2
Order By: Relevance
“…Sample size was calculated based on the experience of previous studies (Chapman et al, 2016(Chapman et al, , 2017 using similar procedures at the same facility and expecting a 90% probability to detect a ≤200 g/d difference in ADG with SE of 100 g/d at P < 0.05. Data were analyzed using the MIXED procedure in SAS (version 9, SAS Institute Inc., Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was calculated based on the experience of previous studies (Chapman et al, 2016(Chapman et al, , 2017 using similar procedures at the same facility and expecting a 90% probability to detect a ≤200 g/d difference in ADG with SE of 100 g/d at P < 0.05. Data were analyzed using the MIXED procedure in SAS (version 9, SAS Institute Inc., Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrients in MR are typically more digestible and are used with greater efficiency than nutrients in starter. Other studies (Diaz et al, 2001;Khan et al, 2007b;Chapman et al, 2017) reported greater feed efficiency in calves fed more milk or MR. However, other studies (Khan et al, 2007a) reported no difference in feed efficiency in calves fed more milk before weaning.…”
mentioning
confidence: 93%
“…Nitrogen intake (NI), N voided through faeces, urine and total N outgo remained unchanged during experimental trial. Chapman et al [22] observed no differences in N intake in Holstein dairy calves fed with high protein milk replacer. The N absorption did not alter with various levels of fat and protein.…”
Section: Nutrient Digestibility and Nitrogen Balance In Sahiwal Calvesmentioning
confidence: 95%
“…This improvement in digestibility of DM, OM, and CP could be due to increase in quantity of better quality nutrients with increase in protein levels of calf starter. Chapman et al [22] reported that calves fed with milk replacer (26% CP, 18% fat) had greater nutrient digestibility for DM, OM and tended to be greater for CP digestibility than the control groups (20% CP, 20% fat). In contrary, feeding of calves with MR (27% CP and 17% fat) at pre-weaning stage leads to decreased OM digestibility of 11% at post-weaning stage [23].…”
Section: Nutrient Digestibility and Nitrogen Balance In Sahiwal Calvesmentioning
confidence: 99%
“…There was no difference between NC and HRTS preweaning for glucose concentrations, supporting previous studies (Omidi-Mirzaei et al, 2015;Chapman et al, 2017). However, plasma glucose was greater in calves HRAS from birth trough week 7 compared to calves fed NC (P = 0.05), possibly as a result of greater liquid feeding and the greater starch intake by cracked corn provided as the main ingredient in AS group until week 4 ( Figure 5).…”
Section: Resultssupporting
confidence: 83%